Sequential IL-23 and IL-17 and increased Mmp8 and Mmp14 expression characterize the progression of an experimental model of periodontal disease in type 1 diabetes - Silva, Juliete A. F.; Ferrucci, Danilo L.; Peroni, Luis A.; Abrahao, Patricia G. S.; Salamene, Aline F.; Rossa-Junior, Carlos [UNESP]; Carvalho, Hernandes F.; Stach-Machado, Dagmar R. (Wiley-Blackwell, 2012)
Molecular mechanisms responsible for periodontal disease (PD) and its worsening in type 1 Diabetes Mellitus (DM1) remain unknown. Cytokine profile and expression levels of collagenases, Mmp14, and tissue inhibitors were determined, as were the numbers of neutrophils and macrophages in combined streptozotocin-induced DM1 and ligature-induced PD models. Increased IL-23 (80-fold) and Mmp8 expression (25-fold) was found in DM1. Ligature resulted in an IL-1 beta/IL-6 profile, increased expression of Mmp8, Mmp13, and Mmp14 (but not Mmp1), and transient expression of Timp1 and Reck in non-diabetics. PD in DM1 involved IL-1 beta (but not IL-6) and IL-23/IL-17, reduced IL-6 and IL-10, sustained Mmp8 and Mmp14, increased Mmp13 and reduced Reck expression in association with 20-fold higher counts of neutrophils and macrophages. IL-23 and Mmp8 expression are hallmarks of DM1. In association with the IL-1/IL-6 (Th1) response in PD, one found a secondary IL-17 (Th17) pathway in non-diabetic rats. Low IL-6/TNF-a suggest that the Th1 response was compromised in DM1, while IL-17 indicates a prevalence of the Th17 pathway, resulting in high neutrophil recruitment. Mmp8, Mmp13, and Mmp14 expression seems important in the tissue destruction during PD in DM1. PD-associated IL-1/IL-6 (Th1), IL-10, and Reck expression are associated with the acute-to-chronic inflammation transition, which is lost in DM1. In conclusion, IL-23/IL-17 are associated with the PD progression in DM1. J. Cell. Physiol. 227: 24412450, 2012. (c) 2011 Wiley Periodicals, Inc.